Introducing the New Editorial Team at the Journal of Experimental Political Science. Issue 1 (22nd March 2018) - Arceneaux, Kevin; Wilson, Rick; Boudreau, Cheryl; Bush, Sarah; Jerit, Jennifer; Sinclair, Betsy; Settle, Jaime; Woon, Jonathan; Zechmeister, Elizabeth
Abstract : We are excited and honored to be the editorial team for JEPS. We are indebted to Eric Dickson for his efforts as the journal's previous editor. He set a high bar for JEPS as an outlet for high quality experimental research. Lucky for us, the healthy state of experimental research means that we will continue to have a deep pool of well-crafted and important work. We also thank Nick Haas, who deftly guided us through the transition as Editorial Assistant. Without his help, it would have been a near impossible task to get up to speed.